Perancangan Sistem Smart Lighting Menggunakan Arduino - Khairunnisa, Khairunnisa; Basyir, Muhammad Khalidin; Siregar, Yustria Handika (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2024)
In Indonesia, many users use electricity for light needs. There are two types of light sources, there is man-made light and there is natural light. The light source also only has two methods, namely turning it on and turning it off. No one can set the conditions for the light, in other words it has to be done manually. Therefore, the cause of electricity waste is manual use. In this case, researchers aim to create a control system for this light. With a system that is able to control the light control system automatically. Through a PIR sensor which will control movement to turn on the lights. The way it works is very easy, if there is movement the light will turn on.  Keywords: Arduino, System, Light